Sociocultural Competence Training in Higher Engineering Education: The Role of Gaming Simulation; Procedia - Social and Behavioral Sciences; Vol. 166 : Proceedings of The International Conference on Research Paradigms Transformation in Social Sciences 2014 (RPTSS-2014) - Galanina E. V. Ekaterina Vladimirovna (2015, 2015)
Title screen